2019
DOI: 10.1590/2318-0331.2431920170167
|View full text |Cite
|
Sign up to set email alerts
|

Experimentation and modeling of soil evaporation in underground dam in a semiarid region

Abstract: In semi-arid regions, there is a high evaporation, which leads to soil dryness, interfering in the availability of water in the soil. Usually it is difficult to measure and model the evaporation due to the complexity of the available methods, the low soil water content and the low concentration of water vapor in the air. This can also make it difficult to monitor and simulate the evapotranspiration in these regions. Thus, the Portable Chamber method is used to directly measure evaporation and evapotranspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
4
0
4
Order By: Relevance
“…The hg parameter presented an average of -3.795 mm, with high variability, according to the Warrick & Nielsen (1980) criteria. Lafayette et al (2019) recorded hg values of -65 and -80 mm for sandy loam soils, while Ursulino et al (2019) verified average hg values of -167 mm for the superficial layer in sandy loam soil. França Neto et al…”
Section: Gcm -3 ] ------[%] -------------[-] -----------mentioning
confidence: 79%
“…The hg parameter presented an average of -3.795 mm, with high variability, according to the Warrick & Nielsen (1980) criteria. Lafayette et al (2019) recorded hg values of -65 and -80 mm for sandy loam soils, while Ursulino et al (2019) verified average hg values of -167 mm for the superficial layer in sandy loam soil. França Neto et al…”
Section: Gcm -3 ] ------[%] -------------[-] -----------mentioning
confidence: 79%
“…A geologia subjacente da região é caracterizada por embasamento cristalino de baixa condutividade hidráulica e baixa capacidade de infiltração. As más propriedades hidráulicas do porão cristalino subjacente significam que o armazenamento e a extração de águas subterrâneas estão limitados a depósitos de aluvião no leito de rios (LAFAYETTE et al, 2019).…”
Section: áRea De Estudounclassified
“…Although, in recent years these types of studies have been considered with the help of modern methods. Lafayette et al (2019) experimented and modeled soil evaporation in an underground dam in the semi-arid region of Pernambuco, Brazil. The results showed that the Simple Soil Plant Atmosphere Transfer (SiSPAT) model was quite satisfactory for simulating soil evaporation under different water depth conditions.…”
Section: Introductionmentioning
confidence: 99%